2014
DOI: 10.1111/apm.12230
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of type I restriction modification system‐negative emm1 type Streptococcus pyogenes clinical isolates in Japan

Abstract: Streptococcus pyogenes emm1 type is the dominant cause of streptococcal toxic shock syndrome (STSS) in Japan and many other developed countries. Recently, the number of STSS patients in Japan was reported to be increasing. Hence, we analyzed the S. pyogenes clinical isolates detected in Japan after 2005. We found that the regions encoding the Spy1908–1910 two-component regulatory system and the adjacent type I restriction modification system were deleted in some emm1 type isolates. The isolates with the deleti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 31 publications
(45 reference statements)
2
13
1
Order By: Relevance
“…Recently, we reported that the regions encoding the SalR–SalK, a two‐component regulatory system, and the adjacent type I restriction modification system were deleted in some emm 1‐type isolates. The isolates with the deletion were detected only in the emm 1 strains that were isolated after 2010 . In this study, we call emm 1 strains with and without the deletion as ‘novel’ and ‘conventional’ emm 1 strains, respectively, unless otherwise stated.…”
mentioning
confidence: 99%
“…Recently, we reported that the regions encoding the SalR–SalK, a two‐component regulatory system, and the adjacent type I restriction modification system were deleted in some emm 1‐type isolates. The isolates with the deletion were detected only in the emm 1 strains that were isolated after 2010 . In this study, we call emm 1 strains with and without the deletion as ‘novel’ and ‘conventional’ emm 1 strains, respectively, unless otherwise stated.…”
mentioning
confidence: 99%
“…The method described here is based on engineering E. coli to express active type I hsdMS genes from S. aureus , but this approach can equally be applied to other bacterial species where type I RM is a barrier to genetic manipulation, such as Streptococcus spp., Staphylococcus spp., and E. coli ( 3 , 22 24 ). Our approach to integrate the hsdMS genes onto the chromosome stabilized the DNA, in contrast to the instability/toxicity observed for hsdMS genes.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that the region encoding the SalR‐SalK, a two‐component regulatory system, and the adjacent type I restriction modification system was deleted in some emm 1‐type isolates . These isolates possessed mef (A) and msr (D) genes in the conjugative prophage Ф1207.3, which are involved in macrolide resistance .…”
Section: Introductionmentioning
confidence: 99%
“…These isolates possessed mef (A) and msr (D) genes in the conjugative prophage Ф1207.3, which are involved in macrolide resistance . A S. pyogenes strain 10–85, which was isolated from a STSS patient, is one of the isolates with the above genetic features consisting of the deletion, the mef (A) possession, and the msr (D) possession . We recently announced the complete genome sequence of strain 10–85 …”
Section: Introductionmentioning
confidence: 99%